ANALISIS JURIDICO ACERCA DEL DERECHO DE LOS NIÑOS, NIÑAS Y ADOLESCENTES A SER ESCUCHADOS RESPECTO A JUICIOS DE TENENCIA Y PATRIA POTESTAD Y SU INCIDENCIA CON EL INTERÉS SUPERIOR DEL NIÑO - Rogel Malla, Fátima Vicenta (2024)
The right of children and adolescents to be heard is a nationally and internationally recognized right, aimed at allowing them to express their opinions on all situations that affect them and in which they are involved, particularly regarding custody and parental authority trials. This research seeks to demonstrate and analyze how the opinions of children and adolescents are essential for judges to render judgments without violating the Principle of the Best Interest of the Child, as well as the rights of equality and the principle of parental responsibility between parents. The analysis adopts a mixed methodology combining surveys, interviews, and documentary analysis. Surveys were conducted on a representative sample of professionals to assess their perception from a legal standpoint regarding the effectiveness of the right of children and adolescents to be heard. Semi-structured interviews were conducted with legal professionals to obtain a broad and diverse understanding of the implications of minors' opinions regarding custody and parental authority. Likewise, a thorough comparative analysis of the family law legislations of other countries regarding custody and parental authority was carried out. Based on these results, recommendations were made regarding the right of minors to be heard, as well as its relationship with the principle of parental responsibility concerning their common children.